Patient expectations predict outcomes following distal radius fracture: a prospective cohort study using the TEFTOM questionnaire. Issue 4 (April 2021) - Fang, Christian; Chen, Yu-Jie; Fang, Evan; Wong, Tak-Man; Liu, Zhao-Hua; Lau, Tak-Wing; Fok, Margaret Woon Man; Yee, Dennis KH; Pun, Terence; Luo, Cong-Feng; Leung, Frankie
Highlights: Patient expectations independently predict outcomes up to twelve months following distal radius fracture. Patient satisfaction is correlated with absolute functional and quality of life outcomes, rather than degree of expectations fulfillment. Patient-reported outcome measures (PROMs) are subject to psychological status and patient attitudes and patient expectations may play a confounding role in research involving PROMs as well as a moderating role in rehabilitation success. Abstract: Introduction: The relationship between patient expectations and clinical outcomes has recently been of increasing interest in the field of orthopaedics. The objective of this study was to evaluate the relationships between (1) patient pre-treatment expectations and post-treatment clinical outcomes, and (2) fulfillment of expectations and patient satisfaction, following distal radius fracture. Methods: This was a prospective multicenter cohort study conducted across three hospitals. A total of 133 patients admitted to hospital between 2016 and 2018 with a distal radius fracture were recruited. Patients were administered the Trauma Expectation Factor (TEF) at baseline to measure expectations of pain and functioning at one-year post-injury. Patients were followed up at 6 and 12 months post-injury and outcomes were measured using the Trauma Outcome Measure (TOM), Shortened Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire, and Short-Form 12-item (SF-12) health survey. Fulfillment of expectations was measured as TEF score minus TOM score at each time point. Patient satisfaction was also measured using the Patient Satisfaction Questionnaire Short Form (PSQ-18). Multivariate regression models were created to evaluate the effect of expectations on outcomes. Results: Patient expectations correlated moderately with outcomes at 6 and 12 months post-injury. In the multivariate analysis, patient expectations were predictive of better outcomes at 6 and 12 months. Injury severity, age, mechanism of injury, and whether the injury occurred on duty also contributed significantly to one or more regression models. Patient satisfaction correlated weakly with fulfillment of expectations at 6 months, but moderately with all outcome scores. At 12 months, satisfaction did not correlate significantly with expectations fulfillment but correlated moderately to highly with all outcome scores. Conclusion: Patient expectations independently predicted outcomes at 6 and 12 months post-injury. Standardized assessment and management of patient expectations may be relevant to future clinical practice and research to best quantify and optimize patient outcomes.